Actualization of Differentiated Learning Approaches in English Subjects In The Merdeka Curriculum Paradigm at Central Bengkulu Senior High School - Febriani, Hanura; Badeni, Badeni; Kristiawan, Muhammad; Risdianto, Eko; Efrizal, Dedi (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2024)
Differentiated learning approach is important to facilitates students to create a conducive learning environment that caters to the unique abilities and requirements of each student. The objective of the research is to investigate the implementation of a differentiated learning approach in the independent learning curriculum paradigm in English language subjects at senior high schools Bengkulu Tengah as well as to analyze the challenges faced by teachers in implementing differentiated learning in the context of the Merdeka Curriculum and their recommendation in implementing differentiated learning approaches in English subjects. This research method is descriptive qualitative by conducting interviews with guru penggerak (change agent teachers) who teach English classes with a differentiated approach. semi-structured interviews were conducted in this research. The result showed in implementing differentiated learning, SMAN 03 Bengkulu Tengah conducts initial diagnostics assessment to determine students' abilities, interests, and learning styles. This finding is slightly different from some previous researchers who implemented differentiated learning by using ability categories, namely low, medium and high. There were some challenged faced by teachers in implementing differentiated learning were inappropriate diagnostic assessment results, time management, limited research because only a small number of teachers have participated in differentiated learning training as driving teachers. Teacher recommended to accommodate a variety of learning styles and it is crucial to receive collaboration and support from the institution. Teachers are required to collaborate with their counterparts in order to develop cross-curricular activities that incorporate a variety of learning styles. Therefore, investigating the implementation of differentiated learning approach is essential in giving contribution to teaching English especially for foreign language.